2019
DOI: 10.1088/1361-6587/ab469f
|View full text |Cite
|
Sign up to set email alerts
|

Particle charge fluctuation and its consequences on aerosol dynamics in dusty plasmas: from continuous to discrete statistical models

Abstract: In this article work we investigated different approaches and models used for the estimation of the charge fluctuation of solid particles in dusty plasmas. We compared the charge distributions inferred from these models and analysed the consequences in terms of coagulation kinetics and particle size distributions. We especially showed that taking explicitly into account the discrete nature of the charging process along with the enhancement of ion flux due to ion-neutral elastic collisions result in significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, under the investigated discharge conditions this mode is largely dominated by negatively charged particles, while the positively charged ones can be completely neglected, i.e. n + p << n (0) p < n − p [24]. Therefore, the coagulation of two particles from the nucleation mode essentially involves a neutral particle and a negative particle.…”
Section: Coagulation Source Termmentioning
confidence: 97%
“…However, under the investigated discharge conditions this mode is largely dominated by negatively charged particles, while the positively charged ones can be completely neglected, i.e. n + p << n (0) p < n − p [24]. Therefore, the coagulation of two particles from the nucleation mode essentially involves a neutral particle and a negative particle.…”
Section: Coagulation Source Termmentioning
confidence: 97%
“…It was shown that, for OML theory of particle charging, the particle charge distribution can be represented as a Gaussian Russell 1995, 1997). However, it has to be noted that charge is discrete and modeling particle charging using a continuous model may not accurately describe the charging process (Michau et al 2019). This is especially the case when the charge fluctuation is of the same order as the average charge, which usually takes place for small solid particles, i.e.…”
Section: Models Of the Kinetic And Thermal Behavior Of Nanoparticles ...mentioning
confidence: 99%
“…Figure 4 shows the charge distribution for nanoparticles of different sizes obtained using Monte Carlo simulations inside a plasma as described in Michau et al (2019). While the Gaussian approximation for charge distribution was appropriate for large particles, such an approximation is no more correct for very small particles.…”
Section: Models Of the Kinetic And Thermal Behavior Of Nanoparticles ...mentioning
confidence: 99%
“…As a result, the dust particles can be distributed in different places of the plasma reactor. In addition, knowledge of the dust charge distribution is very important when describing the coagulation kinetics for nanometre-sized dust particles [43]. Accounting for the charge fluctuations in dust charging models is crucial for dust particles with small charges that can fluctuate with a magnitude comparable to the mean value of the charge [39,42,[44][45][46].…”
Section: Introductionmentioning
confidence: 99%